El mito del cuarto poder en los tiempos de las torres gemelas - Hernando, Bernardino M. (Estudios sobre el Mensaje Periodístico, 2002)
The topics (and the expression “fourth power” it is; since it is already the history of the “twin towers” of New York) they demand increasingly reticence and analysis. What in this moment is happening in the world of the Mass media, even in his more showy and seemingly novel aspects, it has long and deep roots in the past and his branches to the wind point at a future probably more predictable than the future it is in the habit of being. Always with the point of uncertainty that grant the elements that in them intervene: the ambition humanizes, the intelligence and the dignity you humanize, a changeable and uncertain clientele. And the gram of madness that also has hollow in the history of the men.